2021
DOI: 10.1515/med-2021-0263
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of TRIM28 expression in patients with breast carcinoma

Abstract: Background Tripartite motif 28 (TRIM28) plays a role in multiple biological functions. The expression and function of TRIM28 in breast carcinoma (BC) remain unclear. The aim of this study was to explore potential association of TRIM28 with tumor features and survival. Materials and methods Specimens were collected from BC and adjacent normal tissues. Quantitative reverse transcription PCR (RT-qPCR) and immunohistochemistry (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The dysregulation of BrD proteins has been repeatedly acknowledged in different types of cancer. TRIM28 overexpression in breast cancer was correlated with lymph node metastasis and shorter overall survival (OS) [15]. BRD4 was reported to be involved in the development of leukemia, prostate cancer, and breast cancer, as confirmed by BET-inhibitor (BETi) studies [16].…”
Section: Introductionmentioning
confidence: 93%
“…The dysregulation of BrD proteins has been repeatedly acknowledged in different types of cancer. TRIM28 overexpression in breast cancer was correlated with lymph node metastasis and shorter overall survival (OS) [15]. BRD4 was reported to be involved in the development of leukemia, prostate cancer, and breast cancer, as confirmed by BET-inhibitor (BETi) studies [16].…”
Section: Introductionmentioning
confidence: 93%
“…Alteration of TRIM protein expression is suggestive of BC development. TRIM13, 215 TRIM21, 216 TRIM35, 214 TRIM58, 217 and TRIM62 169 are expressed at low levels in BC samples, whereas the expression of TRIM24, 218 TRIM28, 219,220 TRIM39, 211 TRIM44, 175 TRIM59, 221 and TRIM63 177 maintains high. Analyzing the relationship between TRIM expression and clinic‐pathological features of patients, members such as TRIM24, TRIM28, and TRIM59 are revealed further upregulated in the subtype of TNBC which is usually more aggressive.…”
Section: Potential Of Trims In Diagnosis and Drug Designsmentioning
confidence: 99%
“…212 Pathiraja et al observed that ectopic expression of TRIM24 in immortalized HMECs (TRIM24 iHMECs) would activate aerobic glycolysis as well as greatly increase glucose metabolism, and functionally promote the malignant biological behavior of BC. 213 TRIM58, 217 and TRIM62 169 are expressed at low levels in BC samples, whereas the expression of TRIM24, 218 TRIM28, 219,220 TRIM39, 211 TRIM44, 175 TRIM59, 221 and TRIM63 177 maintains high. Analyzing the relationship between TRIM expression and clinic-pathological features of patients, members such as TRIM24, TRIM28, and TRIM59 are revealed further upregulated in the subtype of TNBC which is usually more aggressive.…”
Section: Metabolic Reprogrammingmentioning
confidence: 99%
“…The aberrant expression of the genes encoding bromodomain proteins has been frequently associated with a number of different types of cancer, often showing either a favorable or non-favorable prognostic value [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Global transcriptomic profiling via high-throughput RNA sequencing (RNA-seq) has proven to be a powerful method for classifying gene expression patterns, identifying biomarkers for disease classification and diagnosis, and uncovering candidate drug targets.…”
Section: Expression and Dependency Patterns Of Bromodomain Genes Across Cancermentioning
confidence: 99%
“…Thus, TRIM28 activity contributes to the development of several cancers. For example, TRIM28 is overexpressed in glioma [ 225 ], cervical cancer [ 226 ], lung cancer [ 227 ], hepatocellular carcinoma [ 228 ], and breast cancer [ 50 ]. Overexpression of TRIM28 is often associated with a more aggressive disease and poor patient outcomes, but it is unclear if bromodomain inhibition would be an effective therapeutic strategy since it does not appear to function as a canonical chromatin reader domain.…”
Section: An Interconnected Network Of Functional Groups In Bromodomain Proteinsmentioning
confidence: 99%